Дотримання прав людини у Румунії та Україні: порівняльний аспект - Ніколенко, Христина Михайлівна (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi.
Keywords: Міжнародні відносини, права людини, Румунія, Україна.